Variation of Vp/Vs ratios for granitic layers and weekly average number of earthquakes in NE India (MAUSAM, 2002)
Vp/Vs ratios for the granitic layers in Shillong Plateau and the partially overlapping Tezpur seismic area, have been calculated from Wadati diagrams drawn on the basis of seismic phase data. From Shillong plateau the average of 23 readings for some months of 1979 for Vp/Vs is found to be 1.71. For Tezpur area the average of 29 readings of Vp/Vs for 1991-92 is found to be 1.73, but for 1995-96, the average Vp/Vs from 49 readings is found to be 1.68. The overall average from 78 readings for this area is 1.70. The low Vp/Vs for 1995-97 seems to be precursory. For the granitic layer, taking Vp = 5.92 kms/s and Vp/Vs = 1.70. We get Vs=3.48 km/s for NE India. Values of Vp/Vs ratios and number of shocks per day are plotted against time and are shown to undergo sudden lowering before many M³4.2 earthquakes. Vp/Vs is generally lowered below 1.60 in such cases. In Shillong plateau the number of shocks per day for 1979 is found to be three times the number in the adjoining Tezpur area, for 1991-97.